About the possibility of using the field of the portable neutron generator for treatment of oncological diseases - Stoyanov, A.Ph.; Dovbnya, A.N.; Tsymbal, V.A. (Вопросы атомной науки и техники, 2017)
The possibility of using a portable neutron generator (PNG) for the treatment of oncological diseases is being considered. It has been shown that when using PNG as a neutron source, it is possible to ensure sufficient therapeutic impact on sick cells, with minimal damage to healthy cells. It's about applying PNG in a brachytherapy tumor. It is important to note that the presence of a narrow ion- pipe- needle allows a neutron source to be placed close to the tumor, and thus to increase therapeutic influence. Numerical estimates of the density of neutrons and the consumed dose when using PNG for brachytherapy performed, it is shown that, for a short period of time (~ 1 minute), sufficient dose of radiation for therapy is absorbed. The calculations of the neutron field and absorbed dose are accom-plished through a computer program developed by the authors based on the Monte Carlo method, designed to simulate the generation, movement, braking and absorption of neutrons.